1996
DOI: 10.1152/jappl.1996.81.3.1138
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme inhibition and the norepinephrine spillover response to dynamic exercise

Abstract: To determine whether prejunctional angiotensin II receptors facilitate norepinephrine (NE) release during exercise, normal volunteers exercised at approximately 25 or approximately 65% of maximal O2 consumption (VO2max) on two occasions. Steady-state NE kinetics were determined at rest and during exercise by using infusions of [3H]NE. Arterial plasma NE and [3H]NE were determined for calculation of NE spillover and clearance. Before the second bout of exercise at approximately 25% of VO2max later that day, ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In one human forearm study, intrabrachial AngII infusion during concomitant nitroprusside infusion to offset vasoconstriction was accompanied by an increased concentration of noradrenaline in the forearm venous blood and an increased forearm noradrenaline spillover (Clemson et al 1994). However, several other similar studies, including one by the same group, found no evidence for a functionally significant effect of AngII on noradrenaline release in healthy subjects or in patients with heart failure (Chang et al 1995; Leuenberger et al 1996; Goldsmith et al 1998). In addition, more recent studies, using AT 1 blockade and investigating several vascular beds in humans, have found no support for this mechanism either (Schlaich et al 2005; Krum et al 2006).…”
Section: Discussionmentioning
confidence: 91%
“…In one human forearm study, intrabrachial AngII infusion during concomitant nitroprusside infusion to offset vasoconstriction was accompanied by an increased concentration of noradrenaline in the forearm venous blood and an increased forearm noradrenaline spillover (Clemson et al 1994). However, several other similar studies, including one by the same group, found no evidence for a functionally significant effect of AngII on noradrenaline release in healthy subjects or in patients with heart failure (Chang et al 1995; Leuenberger et al 1996; Goldsmith et al 1998). In addition, more recent studies, using AT 1 blockade and investigating several vascular beds in humans, have found no support for this mechanism either (Schlaich et al 2005; Krum et al 2006).…”
Section: Discussionmentioning
confidence: 91%
“…To date, studies examining the functional importance of the sympathoexcitatory effects of angiotensin II have yielded inconsistent results (9, 11, 24, 26 -28, 40 -42, 44, 60, 61). A number of studies, performed in normal volunteers, have failed to define a sympathomodulatory role of the RAS (9,26,41,44,48). Studies examining sympathetic activity in patients with heart failure have yielded conflicting results concerning the importance of angiotensin II as a mediator of sympathetic activity Values are means Ϯ SE.…”
Section: Discussionmentioning
confidence: 99%